Analysis of Dam Overtopping Failure Risks Caused by Landslide-Induced Surges Considering Spatial Variability of Material Parameters - Dong, Kai; Li, Zefa; Lu, Xiang; Chen, Chen; Sheng, Jinbao; Chen, Jiankang; Wu, Zhenyu (Frontiers in Earth Science, 2021)
Many of the existing reservoir dams are constructed in alpine and gorge regions, where the topography and geological conditions are complicated, bank slopes are steep, and landslides have a high potential to occur. Surges triggered by landslides in the reservoir are one of the major causes of dam overtopping failures. Many factors affect the slope stability of reservoir banks and the height of surges triggered by landslides, such as spatial variability of material properties, speed of landslides, etc. To reasonably evaluate dam overtopping risk caused by landslide-induced surges is a key technology in engineering that is urgent to be solved. Therefore, a novel risk analysis method for overtopping failures caused by waves triggered by landslides induced by bank instability considering the spatial variability of material parameters is proposed in this study. Based on the random field theory, the simulation method for the spatial variability of material parameters is proposed, and the most dangerous slip surface of the reservoir bank slope is determined with the minimum value of the safety factors. The proxy risk analysis models for both the slope instability and dam overtopping are constructed with the consideration of spatial variability of material parameters, and then the dam overtopping failure risk caused by landslide-induced surges is calculated using the Monte-Carlo sampling. The proposed models are applied to a practical engineering project. Results show that the spatial variability of material properties significantly affects the instability risk of slopes, without considering which the risks of slope instability and dam overtopping may be overestimated. This study gives a more reasonable and realistic risk assessment of dam overtopping failures, which can provide technical support for the safety evaluation and risk control of reservoir dams.